The Design and Microstructure Evolution Mechanism of New Cr1.3Ni2TiAl, CoCr1.5NiTi1.5Al0.2, and V0.3CoCr1.2NiTi1.1Al0.2 Eutectic High-Entropy Alloys - Xin Zhang; Haitao Yan; Yao Xiao; Wenxin Feng; Yangchuan Cai (Metals, 2025)
To expand the fundamental understanding of eutectic high-entropy alloys (EHEAs), three novel alloy systems—Cr1.3Ni2TiAl, CoCr1.5NiTi1.5Al0.2, and V0.3CoCr1.2NiTi1.1Al0.2—were rationally designed through synergistic phase diagram analysis and thermodynamic parameter calculations. Comprehensive microstructural characterization coupled with mechanical property evaluation revealed that these alloys possess FCC+BCC dual-phase architectures with atypical irregular eutectic morphologies. Notably, progressive microstructural evolution was observed, including amplified grain boundary density and the emergence of brittle nanoscale precipitates. Mechanical testing demonstrated superior compressive yield strengths in these alloys compared to conventional FCC+BCC EHEAs with ordered eutectic structures, albeit accompanied by reduced fracture strain. The Cr1.3Ni2TiAl alloy exhibited optimal ductility, with a maximum fracture strain of 15.6%, while V0.3CoCr1.2NiTi1.1Al0.2 achieved peak strength, with a compressive yield strength of 1389.5 MPa. Multiscale analysis suggests that the enhanced mechanical performance arises from the synergistic interplay between irregular eutectic configurations, expanded grain boundary area, and precipitation strengthening mechanisms.